Angiogenin mediates paternal inflammation-induced metabolic disorders in offspring through sperm tsRNAs - Yanwen Zhang (Nature Portfolio, 2021)
Paternal environmental inputs can influence various phenotypes in offspring, with important implications for basic biology and public health. Here the authors show that Ang-mediated biogenesis of 5′-tsRNAs in sperm contributes to paternal inflammation-induced metabolic disorders in offspring.